Case Report: Energy- and Nutrient-Dense Formula for Growth Faltering: A Report of Two Cases From India - Kareem, Zahid Ul; Panuganti, Suresh Kumar; Bhatia, Shikha (Frontiers in Nutrition, 2021)
Infants hospitalized for critical illnesses are at a high risk of undernutrition because of increased nutrient requirements (due to increased metabolism) and decreased nutrient intake (due to disease-related problems such as anorexia or feeding difficulties). This can result in a slowing down of their normal growth, referred to as “growth faltering.” Appropriate nutritional management of these infants is extremely important to avoid long-term adverse outcomes. Administration of energy- and nutrient-dense formula (ENDF; 100 kcal energy and 2.6 g protein per 100 mL, with added micronutrients) can be an effective means of increasing the nutrient and energy intake of these children. Despite the high prevalence of undernutrition and growth faltering among pediatric patients in India, there is a paucity of literature on the use of ENDF in Indian infants. Herein, we report the successful use of ENDF for the nutritional management of two infants hospitalized for growth faltering because of severe upper airway obstruction. The aim of nutritional management was to achieve satisfactory weight gain, which can lead to spontaneous resolution of upper airway obstruction. ENDF was initially administered to provide 50–100 kcal/kg/day, and the dose was gradually increased to 160‒185 kcal/kg/day. Both infants tolerated the formula well and showed satisfactory weight gain. These cases clearly demonstrate that early administration of ENDF is an effective means of increasing nutrient and energy intake of critically ill infants, thereby facilitating catchup growth, without any notable adverse effects.